2000
DOI: 10.2134/jeq2000.00472425002900050033x
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of Soil Nitrogen and Microbial Responses following the Sudden Death of Established Turf

Abstract: The stability of nitrogen within a turf‐soil ecosystem is important both for efficient turf management and preventing the contamination of ground water by nitrate. The objective of this study was to quantify responses of the microbial community and the mobility of soil nitrogen following the sudden death of established turf. Twelve‐year‐old turf plots comprising four cool‐season turfgrass species fertilized with five N sources were maintained on an Enfield silt loam (coarse‐silty over sandy or sandy‐skeletal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 14 publications
4
12
2
Order By: Relevance
“…The amount of NO 3 ) leached from the unfertilised controls (bare soil without turfgrass) after 22 months was 155 kg NO 3 -N ha )1 and 109 kg NO 3 -N ha )1 for the high and low irrigation treatments, respectively. As noted above, losses from the controls probably resulted from the absence of turfgrass to utlilise mineralised soil N (Jiang et al, 2000).…”
Section: Nitrogen Leachingmentioning
confidence: 82%
See 2 more Smart Citations
“…The amount of NO 3 ) leached from the unfertilised controls (bare soil without turfgrass) after 22 months was 155 kg NO 3 -N ha )1 and 109 kg NO 3 -N ha )1 for the high and low irrigation treatments, respectively. As noted above, losses from the controls probably resulted from the absence of turfgrass to utlilise mineralised soil N (Jiang et al, 2000).…”
Section: Nitrogen Leachingmentioning
confidence: 82%
“…The amount of N leached from the unfertilised controls (i.e., no turfgrass) after 22 months was 201 and 136 kg N ha )1 for the high and low irrigation treatments, respectively. These losses probably resulted from the absence of turfgrass to utlilise mineralised soil N (Jiang et al, 2000). The N leached was mainly NO 3 ) or organic N depending upon the irrigation treatment ( Figure 2).…”
Section: Nitrogen Leachingmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review on the fate of nitrogen applied to turf, Petrovic (1990) concluded that only a small amount of fertilizer nitrogen (<10%) normally leaches from established turf to groundwater, a finding generally mirrored by other studies (Gold et al 1990; Guillard and Kopp 2004). Jiang et al (2000) have shown that even when the grass is killed, turf sites retain 90% of their accumulated nitrogen during the ensuing year even if no vegetation is replanted. When turf is re-established soon after death, a normal nitrogen retention pattern is restored within three months of reseeding .…”
Section: Introductionmentioning
confidence: 89%
“…The majority of sod farms are sited over aquifers with highly permeable sandy and loamy soils, and potential nitrate loss during production and immediately after sod harvest is a concern. In a study by Jiang et al [7], nitrate loss within an established turf-soil ecosystem was investigated following the sudden death of the turf. The study indicated that nitrate concentration in the water collected at a soil depth of 60 cm below killed turf was elevated beyond that of healthy turf within 2 months following turf death.…”
Section: Introductionmentioning
confidence: 99%